PENGARUH PEMBERIAN PUPUK ORGANIK CAIR NASA (POC NASA) DENGAN DOSIS BERBEDA TERHADAP PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomea reptans poir) - Fidelis Raymundus Bobo Gadi; Nur Aini Bunyani, Maya F.Roman (ADISAM PUBLISHER, 2025)
This study aims to determine the effect of administering NASA liquid organic fertilizer (POC NASA) with different doses on the growth of land spinach (Ipomoea reptans Poir.), and to determine the most effective dose in increasing the growth of the plant. The study was conducted in the greenhouse of the Faculty of Mathematics and Natural Sciences Biology, Universitas Persatuan Guru 1945 NTT for two months, using a Completely Randomized Design (CRD) with five treatments and three replications, namely P0 (control), P1 (1 ml/L), P2 (2 ml/L), P3 (3 ml/L), and P4 (4 ml/L). The parameters observed included plant height, number of leaves, and stem diameter. The results showed that the administration of NASA POC had a significant effect on the growth of land spinach plants. Treatment P2 (2 ml/L) gave the best results on all observed growth parameters. In conclusion, the use of NASA POC at a dose of 2 ml/L is the most effective dose in supporting the growth of land spinach plants